Pengaruh PSAK No. 102 Terhadap Minat Nasabah Cicilan Emas Di BSI KCP Pandaan A. Yani - Prastira, Hirda; Farida, Alimatul; Nizar, Muhammad (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to analyze the effect of the implementation of PSAK No. 102 on customer interest in gold installment products at BSI KCP Pandaan A. Yani. The background of this research is based on the importance of transparency and accountability in murabahah financing transactions to increase customer trust. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to customers. Data analysis was conducted using validity tests, reliability tests, normality tests, linearity tests, and simple linear regression. The results show that the implementation of PSAK No. 102 has a positive and significant effect on customer interest. This indicates that the better the application of sharia accounting standards, the higher the level of customer trust and interest in gold installment products. These findings emphasize the importance of implementing sharia accounting standards in enhancing the attractiveness of Islamic banking products